2018
DOI: 10.12927/hcq.2018.25430
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Related Harms in Canada

Abstract: The rise in harms associated with opioids is an issue of increasing public health importance in Canada. The Government of Canada recently reported 2,816 apparent opioid-related deaths across the country in 2016. Recent 2017 data show that deaths involving fentanyl-related opioids have doubled from January to March as compared to the same time period in 2016 (Government of Canada 2017). Additional measures that provide a better understanding of opioid-related harms, such as hospitalizations and emergency depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Moreover, RDU-only or co-occurring depression and RDU were associated with increased incidence of emergency department (ED) visits 12. Previous observational study showed that opioid poisonings led to 16 hospitalisations per day in Canada 13. In the same study, it was found that substance use also increased ED visits.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, RDU-only or co-occurring depression and RDU were associated with increased incidence of emergency department (ED) visits 12. Previous observational study showed that opioid poisonings led to 16 hospitalisations per day in Canada 13. In the same study, it was found that substance use also increased ED visits.…”
Section: Introductionmentioning
confidence: 95%
“…In the same study, it was found that substance use also increased ED visits. Over the last 5 years, heroin or synthetic opioid poisonings increased the number of ED visits by 10-fold in Alberta, whereas in Ontario, ED visits increased fourfold and doubled due to heroin and synthetic opioid poisonings, respectively 13. A study investigating substance use and intimate partner violence (IPV) showed that cocaine use was associated with IPV among Black men who have sex with men 14.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Canada is the second-largest consumer of prescription opioids in the world after the US, with approximately 4,000 deaths due to opioid poisoning in 2017 alone [ 23 ]. Youth’s opioid-related ED visits have increased by almost 50% in Ontario between 2012–2013 and 2016–2017 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Canada is less affected but has its share of responsibility being the 2nd largest opioid prescriber. 3,4 In the province of Quebec, the opioid problem remains relatively low compared to the rest of Canada, especially when compared to British-Colombia (9,4 vs 25 opioid-related hospitalizations/100 000 habitants) 5 . Both preventing the problem from worsening and improving the current situation rests in large part with surgeons as regular prescribers of opioids.…”
Section: Introductionmentioning
confidence: 99%